1997
DOI: 10.1002/1521-396x(199703)160:1<151::aid-pssa151>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Cu1—xAgxGaTe2 Thin Films

Abstract: Machine engineering has an inherent potential concerning the use of high performance material like Carbon Fibre Reinforced Plastics. The authors show some successful substitutions of formerly conventionally designed components by CFRP‐parts. The examples are taken from several branches of machine engineering, especially from textile machine engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…As shown in Fig. 16 The S decreased with increasing temperature up to 650 K and kept nearly constant above 650 K. The S values of the samples of x ¼ 0 and 0.01 and those of the samples of x ¼ 0.03 and 0.05 were almost the same. The q also decreased with decreasing Ag content.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…As shown in Fig. 16 The S decreased with increasing temperature up to 650 K and kept nearly constant above 650 K. The S values of the samples of x ¼ 0 and 0.01 and those of the samples of x ¼ 0.03 and 0.05 were almost the same. The q also decreased with decreasing Ag content.…”
mentioning
confidence: 68%
“…2 On the other hand, it is known that AgGaTe 2 has a chalcopyrite structure which belongs to the space group I42d. 16 It has also been reported that AgGaTe 2 exhibits quite low n and high S, e.g., room temperature values of the n and the S of a thin film AgGaTe 2 are 10 13 cm À3 and þ900 lV/K, respectively. [5][6][7][8][9][10][11] Recently, single crystals of AgGaTe 2 have been grown and their physical properties have been examined.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…At room temperature the measured values of n and µ are 2.93 × 10 18 cm -3 and 85.32 cm 2 V -1 s -1 . With m* = 1.26m 0 [4,33], we obtained D = 3.367 × 10 -5 m 2 s -1 . If we suppose that the dielectric constant κ = 10 as in CuInSe 2 [2], then F is determined from Eq.…”
Section: Resultsmentioning
confidence: 89%